Legal Reform of the Penalty for Crime of Recruiting and Involving Children in Armed Conflicts in Light of the Provisions of IHL - Alwheebe, Etesam Alabd S.; Ismail, Hosameldin H. (Journal of Law and Legal Reform, 2024)
The study seeks to clarify the extent of the effectiveness of punishment for the crime of recruiting children and their involvement in armed conflicts, and it has been stipulated in the framework of the statute of the International Criminal Court (ICC) that the recruitment of children and their participation in armed conflicts, a war crime that requires individual criminal accountability, but the phenomenon of child soldiers is still continuing and a source Concern for the international community Although international law criminalizes the recruitment and use of children in military operations, it needs concerted efforts to eliminate it, as the legal framework for this phenomenon does not currently require additional development of its rules as much as it needs to activate and apply these rules, in addition to activating the punitive policy through Effective and deterrent penalties to curb this crime as a war crime and to prosecute its perpetrators, The problem, then, is not one of legislation, but one of implementation. Children often pay a very high price during armed conflicts, as they suffer the direct and indirect consequences of hostilities. Children’s participation in armed conflicts has been a widespread phenomenon since antiquity. Therefore, the international community had to intervene to protect them and prohibit their recruitment. Global efforts have been made to eliminate the phenomenon of recruitment and use of children in military operations by prohibiting the recruitment of children in many international documents.